The role of Russian specialists in the establishment of professional music in 20th century Tuva - Suzukey, Valentina Yu. (The New Research of Tuva, 2019)
The article examines the contribution made by Russian professional musicians, composers, choreographers and others in the establishment and development of Tuvan musical culture in the Soviet period. They have been coming  Tuva explicitly for the purpose of setting up musical collectives, training and working with talented Tuvans in the regional educational institutions. This process is considered an example of mutual influence of Soviet (and first of all, Russian) culture on its Tuvan counterpart. This article for the first time examines the life and work of those specialists whose names had been suppressed in the Soviet period as they fell victims to Stalin's purges. The author relied on information from both published works on the history of Tuvan music and original materials.The first to be named is the military bandmaster S. G. Korovin, who became the head of the brass band of the cavalry regiment of the Tuvan people's revolutionary army. He recorded and arranged folk songs, taught Tuvans musical literacy. In the early 1940s, the first group of professionals arrived from the Soviet Union. Among them were composer and conductor of brass orchestra L. I. Izrailevich, flutist and teacher R. G. Mironovich, choir conductor S. I. Bulatov, composer and teacher A. K. Feldman, ballet teacher and master A. V. Shatin, to name only a few. They were engaged in educating musicians, recording and arranging Tuvan musical folklore and also did some original composing. Also worth mentioning is the contribution made by the teachers of children's music school No. 1 of the 1950s-1960s.Educational work of Soviet musicians bore its fruit as soon at the end of their first year in Tuva. The first songs were composed by A. Chyrgal-ool, M. Munsaka, R. Candensis, V. Kok-ool, A. Laptan and others. The first Tuvan professionals formed the core of the troupe of the national musical drama theatre. But the influence was mutual: Russian specialists learned from Tuvan colleagues, too.
Keywords: Tuva; Tuvan history; Russians in Tuva; history of music; Tuvan music; professional art; Soviet specialist; composer